Synthesis and Study of Some fused Substituted 1,3,4-Thiadiazoles and 1,2,4-Triazoles from 4-Chloro- phenoxy acetic acid and 2,4-dichlorophenoxy acetic acid - Mudhar Othman (College of Education for Pure Sciences, 2020)
In this work the synthesis of some substituted 1,2,4-triazoles and five ring system's reported. 2-(4-Chlorophenoxy) acetic acid (S1) was synthesis from corresponding substituted phenol by its reaction with chloroacetic acid in sodium hydroxide solution, the acids  (Q1 and S1) esterified with methanol and sulfuric acid to give esters (Q2 and S2) which converted to acid hydrazides (Q3 and S3) by their reaction with hydrazine hydrate in ethanol.       The acid hydrazides (Q3 and S3) were treated with carbon disulfide in potassium hydroxide solution to give potassium salts (Q4 and S4) the  formed salts were treated with hydrazine hydrate to give substituted          4-amino-1,2,4-triazoles (Q5 and S5).          4-Amino-1,2,4-Triazole (Q5 and S5) were converted to (Q6 and S6),      (Q9 and S9) and (Q10 and S10) by treating with CS2 in  pyridine, urea and chloroacetic acid. While reaction of 4-amino-1,2,4-triazole (Q5 and S5) with phenyl isothiocyanate gave thiosemicarbazide derivatives (Q7 and S7) that converted to N-phenyl substituted 1,2,4-triazole (Q8 and S8).      The structures of the synthesized compounds were confirmed by physical and spectral data.